IL-17A, a possible biomarker for the evaluation of treatment response in Trypanosoma cruzi infected children: A 12-months follow-up study in Bolivia. - Clara Vásquez Velásquez; Graciela Russomando; Emilio E Espínola; Zunilda Sanchez; Kota Mochizuki; Yelin Roca; Jimmy Revollo; Angelica Guzman; Benjamín Quiroga; Susana Rios Morgan; Roberto Vargas Ortiz; Alberto Zambrana Ortega; et al. (Public Library of Science (PLoS), 2019)
BACKGROUND:The National Program for Chagas disease was implemented in Bolivia in 2006, and it greatly decreased the number of infections through vector control. Subsequently, a treatment regimen of benznidazole (BNZ) was started in seropositive school-age children living in certified vector control areas. METHODS AND FINDINGS:We conducted a 12-month follow-up study and seven blood samples were taken during and after the treatment. Serology, conventional diagnostic PCR (cPCR) and quantitative Real-time PCR (qPCR) were performed. Plasma Th1/Th2/Th17 cytokines levels were also determined. Approximately 73 of 103 seropositive children complied with BNZ, with three interruptions due to side effects. To evaluate each individual's treatment efficacy, the cPCR and qPCR values during the final 6 months of the follow-up period were observed. Among 57 children who completed follow-up, 6 individuals (11%) showed both cPCR(+) and qPCR(+) (non reactive), 24 (42%) cPCR(-) but qPCR(+) (ambiguous) and 27 (47%) cPCR(-) and qPCR(-) (reactive). Within 14 Th1/Th2/Th17 cytokines, IL-17A showed significantly higher levels in seropositive children before the treatment compared to age-matched seronegative children and significantly decreased to the normal level one-year after. Moreover, throughout the follow-up study, IL-17A levels were positively co-related to parasite counts detected by qPCR. At the 12 months' time point, IL-17A levels of non-reactive subjects were significantly higher than either those of reactive or ambiguous subjects suggesting that IL-17A might be useful to determine the reactivity to BNZ treatment. CONCLUSIONS:Plasma levels of IL-17A might be a bio-marker for detecting persistent infection of T. cruzi and its chronic inflammation.